Starbucks - 2007 - Karthik, D., (SAGE knowledge. Cases., 2016)
This case describes the financial and non-financial performance of Starbucks, a large organisation provided as on 2007. Howard Schultz, the promoter and chairman of the corporation is disturbed by the decline in the performance of Starbucks, especially the dilution of customer experience. He is required to analyse what happened and adopt a course of action to strengthen Starbucks' performance vis a vis competitive attacks. The participants are required to analyse the situation, generate options for Starbucks and make recommendations for the future, including whether Jim Donald, the current incumbent, needs to be retained as the CEO of Starbucks.